2015
DOI: 10.4238/2015.june.18.21
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for rice flag leaf traits in doubled haploid populations in different environments

Abstract: ABSTRACT. Two rice doubled haploid (DH) populations derived from the crosses of ZYQ8/JX17 and CJ06/TN1 were used to detect quantitative trait loci (QTLs) for flag leaf length (FLL), width (FLW), and angle (FLA) under long-day conditions in Hangzhou (subtropical zone) and short-day conditions in Hainan (tropical zone), China. The four parents differed significantly in all 3 traits. FLL was found to be positively correlated with FLW in the 2 populations. A total of 30 QTLs were identified for flag leaf traits, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…These data indicate that the semi dwarf genes are probably the major QTLs responsible for the pleiotropic phenotypes. In comparison with previous reports (Hittalmani et al, 2002;Hori et al, 2012;Cai et al, 2015), QTLs for PH and yield-related traits were usually detected on these chromosomal regions. Another two QTL clusters on chromosomes 2 and 3 were collocated for several yield and yield-related traits including TGW and GW traits, and their alleles were all from 'TD70' and had enhancing effects.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…These data indicate that the semi dwarf genes are probably the major QTLs responsible for the pleiotropic phenotypes. In comparison with previous reports (Hittalmani et al, 2002;Hori et al, 2012;Cai et al, 2015), QTLs for PH and yield-related traits were usually detected on these chromosomal regions. Another two QTL clusters on chromosomes 2 and 3 were collocated for several yield and yield-related traits including TGW and GW traits, and their alleles were all from 'TD70' and had enhancing effects.…”
Section: Discussioncontrasting
confidence: 85%
“…Recently, studies of QTL mapping for panicle-and yield-related traits have been performed in rice (Liu et al, 2012;Bian et al, 2013;Cai et al, 2015), allowing several important agronomic genes such as qSH1, PLOG1, and qSW5 to be cloned and functionally analyzed (Konishi et al, 2006;Weng et al, 2008;Wang and Li, 2011), which are of great significance for rice breeding and genomics. PE is a typically and quantitatively inherited trait in mapping populations derived from different rice varieties with natural allelic variation (Yamamoto et al, 2001;Qiao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Canopy height in turfgrasses is a function of both stem and leaf extension, a fact that was evident from several significant correlations between HT, stolon (particularly ILEN), and leaf traits (particularly LLEN), further supported by a number of coincident QTL among traits (more so with ILEN and LLEN). Significant positive correlation between plant height and leaf length was also reported in rice (Cui et al 2002; Yan et al 1999), switchgrass (Sripathi et al 2013), and perennial ryegrass (Yamada et al 2004), and co-localized QTL were also evident in some studies (Cai et al 2015; Yan et al 1999), suggesting that the genetic basis of plant height and leaf length are partially overlapping. In the current study, four markers were significantly linked with both traits - two of which were also detected by CIM.…”
Section: Discussionmentioning
confidence: 74%
“…However, QTL colocalization between leaf traits is often lacking or limited, as observed in the current study. QTL correspondence was completely lacking in perennial ryegrass (Yamada et al 2004), centipedegrass (Wang et al 2014), sorghum (Lu et al 2011), and Brachiaria (Thaikua et al 2016), while few colocalized QTL were reported in rice (Cai et al 2015; Liu et al 2015; Wang et al 2012; Yan et al 1999; Zhang et al 2015a) and wheat (Wu et al 2016). In a maize nested association mapping (NAM) population, leaf length and width displayed weak correlations and largely discrete putative causative variants underlying the traits (Tian et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…With the technology development of molecular biology and molecular markers, the molecular genetic maps for many kinds of plants, such as rice (Cai et al, 2015), maize (Zheng and Liu, 2013), pumpkin (Ge et al, 2015), and pepper (Moulin et al, 2015), have been constructed. In addition, finished quantitative trait locus (QTL) mapping for a variety of traits, greatly explained the genetic mechanisms of these traits.…”
Section: Introductionmentioning
confidence: 99%